Implementasi Digitalisasi Merek Dagang Dalam Perspektif Ekonomi Islam Untuk Meningkatkan Kompetitivitas UMKM di Desa Tirta Kencana Kecamatan Rimbo Bujang Kabupaten Tebo - Lubis, Paulina; Isnaeni, Nurida; Ridhwan, Ridhwan; Amri, Ary Dean; Alissa, Evalina; Raudhatul Jannah, Dhivani (JPM MOCCI : Jurnal Pengabdian Masyarakat Ekonomi, Sosial Sains dan Sosial Humaniora, Koperasi, dan Kewirausahaan, 2025)
The implementation of trademark digitalization in Tirta Kencana Village, Rimbo Bujang District, Tebo Regency, aims to enhance the competitiveness of SMEs by integrating technology and Islamic economic values such as transparency, justice, and sustainability. This program includes digital training, the development of management and marketing platforms, and strengthening internet access. As a result, there was a 40% increase in revenue, a growth in the number of customers, and an improved understanding of digitalization and Islamic economics among business owners. Support from the community and digital infrastructure is expected to drive inclusive and sustainable economic growth in the village, while strengthening the competitiveness of SMEs in the local and regional digital markets.